Characterization of Poly(vinylidene Fluoride) Nanofiber-Based Electrolyte and Its Application to Dye-Sensitized Solar Cell with Natural Dyes - Nita Kusumawati; Pirim Setiarso; Agus Budi Santoso; Supari Muslim; Qurrota A'yun; Marinda Mayliansarisyah Putri (Universitas Gadjah Mada, 2023)
The potential of dye-sensitized solar cells (DSSC) as an alternative to depleting fossil fuels has been investigated. To optimize performance and efficiency, the effectiveness of PVDF and PVDF nanofiber (NF) membrane-based electrolytes in suppressing solvent leakage and evaporation in liquid electrolyte systems was evaluated. SEM results for PVDF NF membranes showed the formation of a network with a three-dimensional structure with a diameter of 100–300 nm and an average thickness of 0.14 mm. The Infrared (IR) spectrum shows the electrolyte and polymer-PVDF interactions. Differential Scanning Calorimetry (DSC) curve shows the melting transition of PVDF NF 7.66% lower than PVDF. Efficiency and resistance of DSSC based on natural dyes as measured by multimeter and Electrochemical Impedance Spectroscopy (EIS) at a solar intensity of 100 mW/cm2 showed the highest efficiency of anthocyanin-based DSSC from telang (Clitoria ternatea L.) flower extract. Its use as a photosensitizer in an electrolyte system based on PVDF NF membranes resulted in an efficiency that was not significantly different from that of liquid electrolytes (1.69%).